Special Issue “Recent Developments in Annexin Biology” - Rescher, Ursula (Cells, 2020)
Discovered over 40 years ago, the annexin proteins were found to be a structurally conserved subgroup of Ca(2+)-binding proteins. While the initial research on annexins focused on their signature feature of Ca(2+)-dependent binding to membranes, over the years the biennial Annexin conference series has highlighted additional diversity in the functions attributed to the annexin family of proteins. The roles of these proteins now extend from basic science to biomedical research, and are being translated into the clinic. The research on annexins involves a global network of researchers, and the 10th biennial Annexin conference brought together over 80 researchers from ten European countries, USA, Brazil, Singapore, Japan and Australia for 3 days in September 2019. In this conference, the discussions focused on two distinct themes—the role of annexins in cellular organization and in health and disease. The articles published in this Special Issue cover these two main themes discussed at this conference, offering a glimpse into some of the notable findings in the field of annexin biology.